Pengembangan Produk Kerajinan untuk Mengatasi Tantangan Bisnis di Indonesia Timur - Mawardi, Harry Anugrah (Jurnal Desain Indonesia., 2024)
In the pursuit of Indonesia's ambitious "Indonesia 2045 Vision," this comprehensive research initiative focuses on empowering craft artisans and micro, small, and medium-sized enterprises (MSMEs) in Eastern Indonesia through design innovation. The region, with its vast natural beauty and cultural heritage, is earmarked for development to contribute more significantly to the nation's economy. This study examines the challenges and opportunities in Eastern Indonesia's craft sector and outlines a structured approach to enhance it. Traditional crafts, particularly weaving and handwoven fabric, play a crucial role in sustaining local livelihoods. However, a balance must be struck between production efforts and economic returns, given varying selling prices. Handwoven fabric exhibits higher adaptability to market demand. The research underscores the importance of product direction, sample creation, and quality control in the iterative design process, emphasizing the need for regular communication with artisans. To streamline support, a Product Development Readiness Index is proposed, allowing designers to allocate resources effectively based on artisans' capabilities. In conclusion, this research lays the foundation for enhancing Eastern Indonesia's craft industry through design innovation, aligning with the country's long-term vision. Future research opportunities encompass interdisciplinary collaboration, market diversification, sustainability, and policy analysis to further enrich the craft sector's development.